ADHD Dog: A Virtual Reality Intervention Incorporating Behavioral and Sociocultural Theories with Gamification for Enhanced Regulation in Individuals with Attention Deficit Hyperactivity Disorder - Nikolaos Sergis; Christos Troussas; Akrivi Krouska; Christina Tzortzi; Georgios Bardis; Cleo Sgouropoulou (Computers, 2024)
The need for effective cognitive training methodologies has increased, particularly for individuals dealing with Attention Deficit Hyperactivity Disorder (ADHD). In response to this demand, Virtual Reality (VR) technology emerges as a promising tool to support cognitive functions. Addressing this imperative, our paper introduces ADHD Dog, a VR game designed to aid individuals with ADHD by harnessing the advancements in VR technology and cognitive science. Our approach integrates behavioral and sociocultural theories, alongside gamification, to foster player engagement and reinforce cognitive functions. The theories employed, including operant conditioning and social constructivism, are specifically chosen for their relevance to ADHD’s cognitive aspects and their potential to promote active and context-based engagement. ADHD Dog, grounded in the principles of neuroplasticity and behaviorist methods, distinguishes itself by utilizing technology to amplify cognitive functions, like impulse control, attention, and short-term memory. An evaluation by individuals with ADHD, psychologists and computer scientists yielded promising results, underscoring the significant contribution of blending narrative-driven gameplay with behavioral and sociocultural theories, along with gamification, to ADHD cognitive training.